Proliferation and Osteogenic Differentiation of Mesenchymal Stem Cells on Biodegradable Calcium-deficient Hydroxyapatite Tubular Bacterial Cellulose Composites. Issue 1621 (2014) - Favi, Pelagie; Dhar, Madhu; Neilsen, Nancy; Benson, Roberto
ABSTRACT: Advanced biomaterials that mimic the structure and function of native tissues and permit stem cells to adhere and differentiate is of paramount importance in the development of stem cell therapies for bone defects. Successful bone repair approaches may include an osteoconductive scaffold that permits excellent cell adhesion and proliferation, and cells with an osteogenic potential. The objective of this study was to evaluate the cell proliferation, viability and osteocyte differentiation of equine-derived bone marrow mesenchymal stem cells (EqMSCs) when seeded onto biocompatible and biodegradable calcium-deficient hydroxyapatite (CdHA) tubular-shaped bacterial cellulose scaffolds (BC-TS) of various sizes. The biocompatible gel-like BC-TS was synthesized using the bacterium Gluconacetobacter sucrofermentans under static culture in oxygen-permeable silicone tubes. The BC-TS scaffolds were modified using a periodate oxidation to yield biodegradable scaffolds. Additionally, CdHA was deposited in the scaffolds to mimic native bone tissues. The morphological properties of the resulting BC-TS and its composites were characterized using scanning electron microscopy. The ability of the BC-TS and its composites to support and maintain EqMSCs growth, proliferation and osteogenic differentiation in vitro was also assessed. BC-TS and its composites exhibited aligned nanofibril structures. MTS assay demonstrated increasing proliferation and viability with time (days 1, 2 and 3). Cell-scaffold constructs were cultured for 8 days under osteogenic conditions and the resulting osteocytes were positive for alizarin red. In summary, biocompatible and biodegradable CdHA BC-TS composites support the proliferation, viability and osteogenic differentiation of EqMSCs cultured onto its surface in vitro, allowing for future potential use for tissue engineering therapies.